2017
DOI: 10.1161/strokeaha.117.017420
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Amnesia

Abstract: Amnesia as the main symptom of acute ischemic cerebral events is rare, mostly transient, and easily mistaken for TGA. Although clinical clues are often present, the threshold for performing diffusion-weighted imaging in acute amnesia should be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…Previous studies have proposed temporal lobe ischemia; 5–7 however, many other studies do not support this mechanism, and several major reasons have been presented. First, patients with TGA have no increased risk factors of cerebrovascular disease compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have proposed temporal lobe ischemia; 5–7 however, many other studies do not support this mechanism, and several major reasons have been presented. First, patients with TGA have no increased risk factors of cerebrovascular disease compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…One patient's symptoms had not yet alleviated, but the patient had no obvious vascular abnormalities, indicating that vascular disease is a pathogenesis of TGA. Previous studies have proposed temporal lobe ischemia; [5][6][7] however, many other studies do not support this mechanism, and several major reasons have been presented. First, patients with TGA have no increased risk factors of cerebrovascular disease compared with healthy controls.…”
Section: Hippocampal Ischemia/infarctionmentioning
confidence: 96%
“…Treatment for TGA remains supportive, given its self-limiting nature, with symptoms generally resolving within 24 h. Initial workup generally includes evaluation of multiple etiologies of altered mentation with imaging including an DWI sequence MRI for evaluation of ischemia. 10 Recurrent episodes of TGA remain somewhat rare. One retrospective cohort study found a recurrence rate of 13.7% and furthermore highlighted that migraines were more associated with recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…functioning independently. 42 Additionally, because multiple longterm outcome studies show no increased risk of subsequent strokes in patients diagnosed with TGA, isolated acute transient amnesia is very rarely due to stroke. 34,[36][37][38][39][40] Patients with strokes that involve the hippocampus usually involve other structures, including the ipsilateral occipital lobe, thalamus, and cerebral peduncle.…”
Section: Discussionmentioning
confidence: 99%